THRIPS SPECIES DIVERSITY IN COTTON ECOSYSTEM OF TAMIL NADU AND THEIR MANAGEMENT - K. SENGUTTUVAN*, (The Journal of Research ANGRAU, 2019)
Comprehensive study on cotton thrips diversity in cotton ecosystem of Tamil Nadu was conducted based on thecollection and the random surveys undertaken by the Department of Cotton, Tamil Nadu Agricultural University. Threespecies belonging to three genera in two families of Thysanoptera order were recorded in Coimbatore cottonecosystem.Phylogenetic analysis and diversity indices were completed to identify the species and their variation revealedthe maximum prevalence of Scirtothrips dorsalis (3.25) followed by Thripstabaci (1.34) and Thripspalmi(0.24) whichshowed high diversity of thrips species in cotton ecosystem system and the importance of its management.The dominantspecies of Scirtothrips dorsalis exhibited the tendency to be the most alarming key pest of cotton in Tamil Nadu. It mightbe possible that the abundance and status of diversity of thrips population could be prominent and transimit the TobaccoStreak Virus disease in cotton. Flonicomid 50 WG @ 75 g a.i. ha-1 has recorded significantly lowest reduction of thripspopulation from 7.93 to 0.40 thrips / 3 leaves followed by acephate 75 SP @ 290 g a.i.ha-1 with a population reduction from7.93 to 0.60 thrips per leaf.